Trends and Patterns in Indo-ASEAN Agricultural Trade: Evidence from India (2013-2022) - Chayanika Saikia; Manashi Gogoi (Archives of Current Research International, 2024)
The study investigates the trade dynamics between India and ASEAN, focusing on agricultural trade from 2013-2022. The study examines the growing trade relations with ASEAN in the case of merchandise and agricultural trade. The study’s primary objective is to evaluate trends and variations in trade flows, identify growth patterns, and assess trade intensity. Utilizing the Compound Annual Growth Rate (CAGR), Coefficient of Variation (CV), and Trade Intensity Index, the analysis reveals significant findings that India experienced a consistent trade deficit in agricultural commodities with ASEAN, peaking in 2022. The CAGR for imports (2.2%) and exports (-2.11%) highlights a slower growth rate in agricultural exports than imports. CV analysis shows notable variability in trade values, indicating fluctuating export-import patterns. The Trade Intensity Index results illustrate a higher import intensity than export intensity, underscoring ASEAN’s strong export position relative to India. These insights provide crucial guidance for policymakers to strengthen India’s agricultural trade strategies and address the trade imbalance within the ASEAN region.